Miss Morton and the English house party murder - Lloyd, Catherine, 1963- (Lloyd, Catherine, 1963- Miss Morton mysteries., 2022)
While attending a house party in the countryside, lady's companion to the wealthy widow Mrs. Matilda Frogerton, Lady Caroline Morton finds things not as they seem when an elderly family member is murdered and attempts to solve the crime with an unexpected ally.